PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP PERTUMBUHAN PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2024 - Aisah Aprilia Santi; Istiono (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze the effect of profitability, liquidity, and capital structure on the growth of companies in the property sector listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The study uses a quantitative approach with secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange. The sampling method employs purposive sampling, resulting in a selection of property sector companies that meet the research criteria. Data analysis is performed using multiple linear regression with the assistance of SPSS Version 25. The research results show that simultaneously, profitability, liquidity, and capital structure have a significant effect on company growth. Partially, profitability has a negative and insignificant effect on company growth, indicating that the profit levels generated during the research period have not been able to drive asset growth or business expansion. Liquidity has a negative and insignificant effect on company growth, suggesting that high liquidity reflects excess funds or unsold inventory, making it unproductive in driving business growth. Meanwhile, capital structure has a negative and significant effect on company growth, indicating that debt-based external financing is one of the main factors enabling companies to expand their assets, as managing debt optimally can provide a leverage effect that boosts company growth